Sea Nono Heu dan Martabat Wanita dalam Tradisi Perkawinan Adat Masyarakat Suku Amarasi di Timor - Moses Kollo; Yanrini Martha Anabokay; Diana Rohi (Jurnal Artefak, 2023)
Sea Nono Heu. Sea Nono Heu is a custom in traditional marriage owned by the Amarasi Tribe community in Timor, East Nusa Tenggara region. This study aims to describe "The process of implementing the traditional sea nono heu ritual for the Amarasi Tribe community in Timor. The location for the implementation of this research is the Amarasi area on Timor Island. This research uses qualitative methods. Research data were collected using interviews, observation, and literature review techniques. Research data is analyzed through three stages of qualitative analysis: data reduction, data presentation, and conclusion drawing or verification. The results of this study revealed that the Amarasi Tribe is a tribe found on the island of West Timor with a traditional marriage tradition called Sea Nono Heu. Sea Nono Heu is the final stage in a series of traditional marriages of the Amarasi Tribe on the island of Timor. At this stage, a bride or groom has the right to pin his surname for the wife after he has completed or completed several customary requirements as determined by the wife's family (bride). The customary requirements are paying belies (dowry), salendang, betel nut, and a female cow. There are three stages in the implementation of Sea Nono Heu, namely the planning stage, the implementation stage, and the closing stage. The people involved in the execution of Sea Nono Heu are the bride and groom (bride and groom), the biological parents of the bride and groom, the extended family of the bride and groom, and other guests.